Bottom-Up Electrodeposition of Zinc in Through Silicon Vias. Issue 3 (1st January 2015) - Josell, D.; Moffat, T. P.
Abstract : This paper describes superconformal feature filling during zinc electrodeposition in a sulfate electrolyte. Localized bottom-up filling of Through Silicon Vias (TSVs) with no deposition on the sidewalls or the field around them is demonstrated in electrolytes containing a deposition rate suppressing additive. This behavior is seen when feature filling proceeds at potentials in proximity to where suppression breakdown and localized zinc deposition are noted in electroanalytical measurements with planar rotating disk electrodes. The favorable comparison with previous results for bottom-up feature filling of Cu, Au and Ni further demonstrates the central role of additive-derived negative differential resistance (NDR) in extreme bottom-up feature filling.